Collaborative Innovation Between SMEs and Startups: Open Business Model Implementation in Batam - Deu, Indasari; Chow, Christina (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2025)
This study explores the collaboration between Small and Medium Enterprises (SMEs) and startups in Batam, emphasizing open business model implementation and co-creation strategy. Using qualitative methods through case study and literature review, this research reveals that collaborative efforts enable SMEs to gain access to technological innovation, flexible funding, and digital transformation support at the same time, startups gain from market opportunities and real-world validation. Despite differences in organizational culture and technological readiness, collaboration enhances mutual value creation and competitiveness in the digital era.